Severe Vulvar and Perianal Crohn's Disease: A Case Report and Review of the Literature - Guillaume Le Cosquer; Alexis Barranca; Louise Lapotre; Eline Casassa; Benoit Chaput; Jonathan Ciron; Louis Buscail; Carle Paul; Cyrielle Gilletta (Karger Publishers, 2022)
Association of vulvar Crohn's disease (CD) with pyoderma gangrenosum (PG) has been described, yet due to its low prevalence, data on therapeutic management of this association are still limited. We here present a 22-year-old woman with severe vulvar and perianal CD with a major inguinal and perineal ulceration. In the hypothesis of an associated PG, oral corticosteroids were prescribed at a dose of 40 mg with limited efficacy for a duration of 3 months. Afterward, a combination treatment of cyclosporine and infliximab followed by negative pressure wound therapy and split-thickness skin graft resulted in complete healing.